Psychological characteristics of Canadian Olympic Games swimmers - Rushall, B. S.; Jamieson, J.; Talbot, D. (1976)
The 1976 Canadian Olympic Games Swimming Team was assessed on the Psychological Inventories for Competitive Swimmers. Comparisons of individual question responses were made between male (N = 20) and female (N = 17) team members and those who improved their personal best performances at the Games (N = 20) and those who did not (N = 17). The results showed a set of characteristics common to the groups as well as sets of differentiations. Male and female Olympic swimmers were sufficiently different to warrant the recommendation of separate future teams for each sex. The features which were peculiar to female swimmers are listed. Swimmers who performed personal best swims in the Olympic Games were discriminated from those who failed to improve on a number of factors. Factors which were peculiar to those who improved are listed also. Implication: Female swimmers had a different set of needs, were motivated differently, and required a specific form of handling to that required of male swimmers. Based on this 1976 finding, for the following decade Canadian Swimming Teams were separated on the basis of sex while enjoying their finest international performances in the history of the sport. There were different behaviors exhibited by successful international performers to those who were unsuccessful. The distinguishing characteristics suggest some reasonable expectations for swimmers in the way they should act and think if success is a personal goal.